A genome-wide association study of bitter and sweet beverage consumption. (2nd May 2019) - Zhong, Victor W; Kuang, Alan; Danning, Rebecca D; Kraft, Peter; van Dam, Rob M; Chasman, Daniel I; Cornelis, Marilyn C
Abstract: Except for drinking water, most beverages taste bitter or sweet. Taste perception and preferences are heritable and determinants of beverage choice and consumption. Consumption of several bitter- and sweet-tasting beverages has been implicated in development of major chronic diseases. We performed a genome-wide association study (GWAS) of self-reported bitter and sweet beverage consumption among 370 000 participants of European ancestry, using a two-staged analysis design. Bitter beverages included coffee, tea, grapefruit juice, red wine, liquor and beer. Sweet beverages included artificially and sugar sweetened beverages (SSBs) and non-grapefruit juices. Five loci associated with total bitter beverage consumption were replicated (in/near GCKR, ABCG2, AHR, POR and CYP1A1/2 ). No locus was replicated for total sweet beverage consumption. Sub-phenotype analyses targeting the alcohol, caffeine and sweetener components of beverages yielded additional loci: (i) four loci for bitter alcoholic beverages ( GCKR, KLB, ADH1B and AGBL2 ); (ii) five loci for bitter non-alcoholic beverages ( ANXA9, AHR, POR, CYP1A1/2 and CSDC2 ); (iii) 10 loci for coffee; six novel loci ( SEC16B, TMEM18, OR8U8, AKAP6, MC4R and SPECC1L-ADORA2A ); (iv) FTO for SSBs. Of these 17 replicated loci, 12 have been associated with total alcohol consumption, coffee consumption, plasma caffeine metabolites or BMI in previous GWAS; none was involved in known sweet and bitter taste transduction pathways. Our study suggests that genetic variants related to alcohol consumption, coffee consumption and obesity were primary genetic determinants of bitter and sweet beverage consumption. Whether genetic variants related to taste perception are associated with beverage consumption remains to be determined.